MARNI'S STRUGGLE AGAINST GENDER INEQUALITY IN OKKY MADASARI'S THE YEARS OF THE VOICELESS - Mochammad Ikhsan Aziz (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2023)
Abstrak The Years of The Voiceless menceritakan tentang seorang perempuan Jawa buta huruf yang berjuang melawan ketidaksetaraan gender untuk kebebasannya di masyarakat Patriarki. Marni adalah karakter utama dalam novel yang mampu mengubah hidupnya melalui mobilitas sosial dari orang termiskin menjadi orang terkaya di desanya. Marni melawan ketidaksetaraan gender dengan mematahkan stereotip negatif pada perempuan yang kemudian membawanya pada kemandirian. Tujuan dari penelitian ini adalah untuk mendeskripsikan ketidaksetaraan gender pada novel tersebut dan mengungkap perjuangan Marni dalam melawan ketidaksetaraan gender pada The Years of The Voiceless. Pendekatan penelitian ini dibagi menjadi tiga bagian: sumber data, pengumpulan data, dan analisis data. Data tersebut diperoleh dari kalimat, ungkapan, dan kejadian dari The Years of The Voiceless. Menggunakan data kualitatif, penelitian ini menunjukkan bahwa The Years of The Voiceless mengungkapkan penderitaan yang dialami oleh Marni dalam menghadapi stereotip negatif, subordinasi, marginalisasi, dan kekerasan terhadap perempuan. Dia diremehkan oleh lingkungannya, khususnya ketika dia ingin bekerja dan mendapatkan uang. Tetapi, melalui mimpinya untuk memiliki sebuah bra, dia mampu meningkatkan kesadarannya yang menjadikannya seorang perempuan yang mandiri. Kata Kunci: ketidaksetaraan gender,feminism, patriarki, perjuangan Abstract The Years of The Voiceless tells about an illiterate Javanese woman who struggles against gender inequality for independence in a patriarchal society. Marni is the main character of the novel who is able to change her life through her social mobility from the poorest to become the richest person in her village. Marni against gender inequality by breaking the negative stereotypes towards women that bring her into independency. The purpose of the study are depicting gender inequality in Okky Madasari’s The Years of The Voiceless and revealing Marni’s struggle against gender inequality in Okky Madasari’s The Years of The Voiceless. The approach of this study is divided into three parts: source data, data collecting, and data analysis. The data was derived from sentences, utterances, and events from The Years of The Voiceless. Using qualitative data, this research shows that The Years of The Voiceless reveals adversities faced by Marni from negative stereotypes, subordination, marginalization, and violence against women. She is underestimated by her society, especially when she wants to work and earn money. Yet, by her dream of having a bra, she could gain her awareness that brings her to become an independent woman. Keywords: gender inequality, feminism, patriarchy, struggle